Plan De Gestión Para La Recolección De Desechos Sólidos En La Ciudad De Huaquillas - Vidal Peñaranda, Zoilo Silverio (2017)
Ecuador has been affected, just like other Latin American countries, by population growth in urban areas, resulting in an uncontrolled volume of solid waste and its inadequate collection procedure because of the little importance that the authorities in charge give to this problem. Although COOTAD makes municipalities responsible for the handling of waste and solid waste (DyRS), the Ministry of the Environment creates the PNGIDS to collaborate in this area. Effective environmental protection requires the prevention of pollution through the combination of materials and processes or practices that minimize waste. Separation of waste components is an important step in the management and storage of waste. The research carried out in this project focuses on a general objective, which is to generate a management plan for the collection of solid waste in Huaquillas city through bibliographical research and technical interviews. All this, to improve the hygiene and salubrity conditions of the population. The specific objectives are to determine the management plans for the collection of solid waste that exist in Huaquillas, its characteristics and scope and evaluate these plans at a global and Latin American level, as well as their impact on the health of the population in order to design a management plan of the DyRS for this city that reduces the impact of pollution. This research has a qualitative approach. The information has been obtained through bibliographic analysis and field research. Have been conducted interviews in primary sources, extensive research in several scientific publications, in addition to direct observation of the phenomenon. According to interviews carried out with the staff of the Department of Environmental Sanitation of the Huaquillas GAD, the analysis of bibliographic information of scientific articles and the direct observation of different sectors of the city (including landfill), it was determined that Huaquillas doesn’t have any management plan for the collection of solid waste. In this city the daily collection of waste is carried out without any planning, evaluation or improvement process. It is concluded that Huaquillas city needs an optimized solid waste collection management plan. The components of this plan are sectorization, design of collection routes, establishment of collection frequencies, evaluation and acquisition of vehicles and collection equipment, among others. This management plan can be strengthened through privatization, in emergencies and includes conferences and talks for the population and workers, raising awareness in the community.